Increased immune cell infiltration of the exocrine pancreas: a possible contribution to the pathogenesis of type 1 diabetes - Rodriguez-Calvo, Teresa; Ekwall, Olov; Amirian, Natalie; Zapardiel-Gonzalo, Jose; von Herrath, Matthias G (Diabetes (New York, N.Y.), 2014)
Type 1 diabetes (T1D) results from a complex interplay between genetic susceptibility and environmental factors that have been implicated in the pathogenesis of disease both as triggers and potentiators of β-cell destruction. CD8 T cells are the main cell type found in human islets, and they have been shown in vitro to be capable of killing β-cells overexpressing MHC class I. In this study, we report that CD8 T cells infiltrate the exocrine pancreas of diabetic subjects in high numbers and not only endocrine areas. T1D subjects present significantly higher CD8 T cell density in the exocrine tissue without the presence of prominent insulitis. Even T1D donors without remaining insulin-containing islets and long disease duration show elevated levels of CD8 T cells in the exocrine compartment. In addition, higher numbers of CD4(+) and CD11c(+) cells were found in the exocrine tissue. Preliminary data in type 2 diabetic (T2D) subjects indicate that overall, there might be a spontaneous inflammatory infiltration of the exocrine tissue, common to both T1D and T2D subjects. Our study provides the first information on the precise tissue distribution of CD8 T cells in pancreata from T1D, T2D, autoantibody-positive, and healthy control subjects.